Validating a composite endpoint for acceptability evaluation of oral drug formulations in the pediatric population: a randomized, open-label, single dose, cross-over study - Münch, Juliane; Schwarzwälder, Anna Lena; Kloft, Carolin; Bosse, Hans Martin; Wargenau, Manfred; Reidemeister, Sibylle; Klingmann, Ingrid; Klingmann, Viviane (Frontiers in Pharmacology, 2024)
Objective: This study aimed to validate the newly developed composite acceptability endpoint to investigate acceptability of oral pediatric drug formulations that integrates swallowability and palatability assessments. Methods: In this open-label study acceptability of oral formulations was tested in 3 age groups (1 - <6 months, 6 - <12 years, and 12 - <18 years) with a 2-way cross-over design in children aged 1 - <6 months (syrup and mini-tablets), and with an incomplete block design of 4 sequences with 3 out of 4 formulations (syrup, mini-tablets, oblong tablet, and round tablet) each in children aged 6 - <18 years. The primary endpoint was acceptability derived from the composite acceptability endpoint. Secondary endpoints were palatability and acceptability derived from swallowability. Results: A total of 320 children were stratified into 3 age groups (80 children aged 1 - <6 months, 120 children aged 6 - <12 years, and 120 children aged 12 - <18 years). All participants completed the study. Age-specific differences were observed in acceptability derived from the composite acceptability endpoint. Mini-tablets had the highest acceptability in participants aged 1 - <6 months and 6 - <12 years while the oblong tablet was leading in adolescent participants (12 - <18 years). Conclusion: This study demonstrated that the composite acceptability endpoint method integrating both swallowability and palatability assessments is a sensitive method to assess acceptability of drug formulations in children of different age.